(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Artificial reefs are artificial habitats laid in waters by mimicking some of the characteristics of natural reefs; and could be made of different materials, one of which is concrete. Seashell waste and stone ash could be added as an alternative material to the concrete for artificial reefs. The purpose of this research is to access the growth rate of Acropora muricata coral fragments transplanted on the hollow dome-shaped concrete with three different compositions: C1), conventional concrete, composed by a mixture of Portland cement, sand, and gravel (composition was 1:3:2); C2), a mixture of Portland cement, sand and crushed bivalve’s shells (composition was 1:3:2); and C3), a mixture of Portland cement, stone waste (stone dust), sand and crushed bivalve’s shells (composition was 1:3:3:2). Observation of coral fragment growth was conducted underwater by Scuba diving for 6 months with observed parameters were fragment length, colony diameter and number of branching. The highest rate of fragment lengthening of A. muricata coral fragment was at C2 (1.019±0.081 cm/month) and C1 (1.014±0.076 cm/ month). The highest colony diameter increment was also in C2 (1.903±0.212 cm/month) and C1 (1.856±0.219 cm/month); while largest number of branches was also in C2 (13.31 or 2.21 branch/month) and C1 (12.56 or 2.09 branch/month), respectively. Based on one-way ANOVA and Tukey’s HSD test (p = 0.05), there is no significant difference in fragment lengthening and colony diameter in C1 and C2 model, yet differed significantly with C3 model.